ANALISIS PENGARUH STRUKTUR ASET DAN KEBIJAKAN DEVIDEN TERHADAP NILAI PERUSAHAAN (Study Pada Perusahaan property Yang Terdaptar di Bursa Efek Indonesia( BEI)Tahun 2013-2015) - Murah (LPPM Universitas Gunung Rinjani, 2019)
This research is intended to test the variables indevenden (Asset Structure and Dividend Policy)which is expected to affect the dependent variable (Corporate Value) either partially orsimultaneously. To know how big influence of asset structure and dividend policy to companyvalue, hence in use statistic analysis tool that is SPSS 20. Technique analyze data that use isdoubled linear regression. While to test the formulation of hypothesis in use Test f and Test t.The population of this study is a property company listed in Indonesia Stock Exchange (BEI)period of 2012-2015 as much as 45. Samples are in use as much as 7 which is obtained bypurposive sampling technique. The data used is secondary data. F test results show that theAsset Structure and the Dividend Policy have no effect simultaneously on firm value. This canbe proved by looking at F count> F table (1,127> 3,555) and significance level 0.881b <0.05.While t test (partial) asset structure and dividend policy do not partially influence to companyvalue. Where the significance level for the asse structure of 0.855 is greater than 0.05 and thevalue of t arithmetic equal to = 0.186 bigger than t table 2.10092. For dividend policy value ofsignificance equal to 0,505 smaller than 0,05 and t value 0,006 bigger than t table equal to2,10092.